Isolated oculomotor nerve palsy due to mesencephalic infarction diagnosed by ZOOM DWI - Shangpei Wang; Yajie Cai; Xiaosan Wu; Sunhong Yan; Longsheng Wang (BMC Neurology, 2025)
Abstract Background Oculomotor nerve palsy is a common neurological presentation in daily practice. Case presentation A 55-year-old man presented with a 3-h history of diplopia and drooping of his bilateral especially left eyelids. Examination revealed an isolated oculomotor nerve palsy consisting of left medial rectus, inferior oblique, superior rectus, inferior rectus with intact pupillary reflexes and bilateral especially left superior palpebral levator. Conventional diffusion weighted imaging (DWI) of the brain showed a suspicious restriction in the left midbrain periaqueductal region. If the clinical symptomatology indicates a lesion in the midbrain, of which a high signal intensity was encountered from neurologically healthy older adults, the limited spatial resolution of conventional axial DWI is an enormous disadvantage. Zonally magnified oblique multislice (ZOOM) DWI correlated with apparent diffusion coefficient map providing higher accuracy for accurate diagnosis can identify signal alterations of mesencephalic interpeduncle area. Conclusions This is a rare presentation of isolated oculomotor nerve palsy due to pure mesencephalic infarction especially verified by ZOOM DWI.